(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article explores the effective methods of improve reading skills and helpful modern strategies to new learners. By examining latest researches and practice in this field, teaching reading skills is taken into account in not only Uzbekistan but also, all around the world. That is why this article provides beneficial techniques that instructors are using to enhance reading profiency among students at the beginning stage of their learning journey.